Morphological characteristics and phylogenetic analyses revealed three new wood-inhabiting fungi (Agaricomycetes, Basidiomycota) in Southern China - Yuan, Qi; Luo, Kai-Yue; Zhang, Ying; Zhao, Chang-Lin (Phytotaxa, 2023)
Fungi are one of the most diverse groups of organisms on Earth, among which wood-inhabiting fungi play a crucial role in ecosystem processes and functions. Three wood-inhabiting fungi belonging to the genera Ceraceomyces, Stereopsis, and Xenasmatella were found in Southern China. Combined with morphological characteristics and molecular biological evidence, the present study describes them to be new fungal taxa Ceraceomyces yunnanens, Stereopsis yunnanens, and Xenasmatella bambusicola. Ceraceomyces yunnanens is distinguished by the resupinate basidiomata with merulioid hymenial surface, monomitic hyphal system and cylindrical basidiospores; S. yunnanensis is characterized by the laterally stipitate basidiocarps with greyish brown to brown pilei, monomitic hyphal system and subglobose basidiospores; and X. bambusicola is characterized by the resupinate basidiomata, arachnoid hymenophore with white to greyish hymenial surface and warted basidiospores. Sequences of ITS and nLSU rRNA markers of the studied samples were generated, and phylogenetic analyses were performed with maximum likelihood, maximum parsimony, and Bayesian inference methods. The phylogenetic analyses of ITS+nLSU showed that three new species nested into families Amylocorticiaceae, Stereopsidaceae and Xenasmataceae (Agaricomycetes), in which C. yunnanens grouped sister to C. borealis; S. yunnanensis grouped with S. radicans; and X. bambusicola grouped sister to X. xinpingensis.